1999
DOI: 10.1037/0012-1649.35.5.1223
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and intellectual differences in self-report and strategy use.

Abstract: The veridicality and reactivity of children's self-report of covert and overt memory strategies were investigated in a task allowing a direct comparison of self-report and the strategy observed. External memory strategies (e.g., moving objects) were investigated with 7-, 9-, 11-, and 17-year-old typical children and 11- and 17-year-old children with mild mental retardation. Participants placed objects in specified spatial locations after hearing sequences of tape-recorded sentences. After each trial, half of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 26 publications
2
17
0
2
Order By: Relevance
“…By comparing the extent to which second and sixth graders' interview data correspond to their performance data, we could assess the development of this task-related metacognitive knowledge and understanding with age (Bray, Huffman, & Fletcher, 1999;Ericsson & Simon, 1980, 1993. More specifically, we will focus on three questions: (a) Are there any significant differences in second and sixth graders' verbal reports?…”
Section: Resultsmentioning
confidence: 99%
“…By comparing the extent to which second and sixth graders' interview data correspond to their performance data, we could assess the development of this task-related metacognitive knowledge and understanding with age (Bray, Huffman, & Fletcher, 1999;Ericsson & Simon, 1980, 1993. More specifically, we will focus on three questions: (a) Are there any significant differences in second and sixth graders' verbal reports?…”
Section: Resultsmentioning
confidence: 99%
“…Russo, Johnson, and Stephens (1989) defined veridicality as the degree to which children's reports correspond to criterion observational measures. Bray, Huffman, and Fletcher (1999), in one of the few studies that has systematically examined both strategy use and children's self-reported use, demonstrated with an intellectually diverse sample of 7-, 9-, 11-, and 17-year-olds that children's verbal reports of external strategies (observable behavioral and motor strategies) used during a location memory task are accurate but often incomplete. That is, children do in fact use the strategies they report using, but they often use additional strategies as well that go unreported.…”
mentioning
confidence: 99%
“…Weldon & Roediger, 1987) was assumed to be essential to successful PM performance in the ID group due to reduced load on limited working memory capacity, language and strategic skills (Bray, 1999). Instead, pictures were essential at retrieval.…”
Section: Pictures and Verbal Prospective Memory Cuesmentioning
confidence: 99%
“…Strategic processing is often limited in persons with ID (Bray, Huffman, & Fletcher, 1999). Shifting between different (some abstract) strategies is more likely for individuals without ID than for the ID group (Bray et al, 1999). Persons with ID usually perform better on memory tasks loading primarily on automatic rather than strategic memory processing (Wyatt & Conners, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation